Ecophysiological groups of garlic cultivars: the updated Argentinean classification - Portela, Jose Antonio; Lanzavechia, Silvina Beatriz; Lopez, Aldo Miguel; Burba, Jose Luis (International Society for Horticultural Science, 2021)
Presentado al VII International Symposium on Edible Alliaceae